2012
DOI: 10.1002/wrna.1131
|View full text |Cite
|
Sign up to set email alerts
|

Intronic features that determine the selection of the 3′ splice site

Abstract: Most eukaryotic primary transcripts include segments, or introns, that will be accurately removed during RNA biogenesis. This process, known as pre‐messenger RNA splicing, is catalyzed by the spliceosome, accurately selecting a set of intronic marks from others apparently equivalent. This identification is critical, as incorrectly spliced RNAs can be toxic for the organism. One of these marks, the dinucleotide AG, signals the intronic 3′ end, or 3′ splice site (ss). In this review we will focus on those intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Some previous studies have investigated the efficiency of splicing either for a specific intron or systematically for all introns, and under a variety of environmental conditions or in varying genetic backgrounds (Pleiss et al 2007;Bergkessel et al 2011;Pérez-Valle and Vilardell 2012). Such studies have demonstrated that different introns exhibit a large range of SEs under varying conditions and have diverse proteinaceous requirements (Clark et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have investigated the efficiency of splicing either for a specific intron or systematically for all introns, and under a variety of environmental conditions or in varying genetic backgrounds (Pleiss et al 2007;Bergkessel et al 2011;Pérez-Valle and Vilardell 2012). Such studies have demonstrated that different introns exhibit a large range of SEs under varying conditions and have diverse proteinaceous requirements (Clark et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…3A). This mutant had 18 nt less relative to wild-type I2, but all intronic features relevant for splicing were well within functional range: the total size of the mutant intron was 52 nt (the minimum size has been proposed to be 50 nt), the distance between the 5 ′ SS and the BS was 28 nt (greater than the required 25 nt minimum), and there were 12 nt between the BS and the 3 ′ SS (10 nt are necessary in this case as a minimum) (Meyer et al 2011;Pérez-Valle and Vilardell 2012). To evaluate the expression efficiency of this mutant in vivo, we used the CUP1 reporter system (Lesser and Guthrie 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The UV-thermal denaturation experiments showed that this intron 2 hairpin had surprisingly low thermal stability. It is well established that both the BS and the PPT of the introns need to be single-stranded to allow binding of the BBP (SF1 in mammals) and Mud2 (U2AF 65 ) proteins in the first steps of spliceosome assembly (Gahura et al 2011;Pérez-Valle and Vilardell 2012). It is therefore remarkable that two of the BS nucleotides (A 45 and C 46 ) and the complete PPT of I2 are contained in the base-paired stem of the I2 hairpin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is usually accomplished by modulation of the accessibility or spatial distribution of splicing signal sequences via base-pairing [76] but also through the presence of more complex folds like riboswitches and ribozymes [77]- [80]. In yeast, for example, the RP51B gene contains a predicted stem-loop that brings the 5' and 3' splice sites into closer proximity.…”
Section: Pre-mrna Structure and Gene Expressionmentioning
confidence: 99%